Fuel Properties and Thermal Processing of Bio-oil and Its Derived Fuel Mixtures - Gao, Wenran (Curtin University, 2018)
This thesis reports the fuel properties and thermal processing of bio-oil derived fuel mixtures. Biochar loading level affects fuel properties and ignition behavior of slurry fuels prepared from crude glycerol/methanol/bio-oil (CGMB) blends and biochar, while exhibits little effect on cold flow behavior. Crude glycerol (CG) improves the ignition and cold flow behavior of slurry fuels while has limited effect on fuel properties. Interactions between sugar and lignin-derived oligomers contribute bed agglomeration during bio-oil fast pyrolysis.